Development of Red Exciplex for Efficient OLEDs by Employing a Phosphor as a Component - Zhang, Ming; Wang, Kai; Zheng, Cai-Jun; Wang, De-Qi; Shi, Yi-Zhong; Lin, Hui; Tao, Si-Lu; Li, Xing; Zhang, Xiao-Hong (Frontiers in Chemistry, 2019)
Exciplexes are one of the ideal candidates as the effective thermally activated delayed fluorescence (TADF) emitters. However, seldom efficient orange and red TADF exciplexes have been reported, because their significant non-radiative (NR) decays of excited states lead to unavoidable energy loss. Herein, we propose a novel strategy to construct efficient red TADF exciplexes by introducing a phosphor as one component. Due to the strong spin−orbit coupling of heavy metal (e.g., Ir, Pt, et al) ion cores, the NR decays will be evidently decreased for both singlet and triplet excitons, reducing the undesired exciton waste. Moreover, compared with the conventional exciplexes, phosphorescence plays an important role for such novel exciplexes, further improving the exciton utilization. Based on this strategy, we fabricate a red exciplex containing 1,3,5-triazine-2,4,6-triyl)tris(benzene-3,1-diyl)tris(diphenylphosphine oxide) (PO-T2T) and tris(2-phenylpyridine) iridium(III) (Ir(ppy)3) as components and realize a red emission with a peak at 604 nm, a CIE coordinate of (0.55, 0.44), and a high maximum external quantum efficiency of 5% in organic light-emitting device. This efficiency is 2.6 times higher than that of the device based on the conventional red exciplex emitter, proving the superiority of our novel strategy to construct red TADF exciplexes with phosphors.